Radical‐Mediated Thiol‐Ene Strategy: Photoactivation of Thiol‐Containing Drugs in Cancer Cells. (2nd November 2018) - Sun, Shuang; Oliveira, Bruno L.; Jiménez‐Osés, Gonzalo; Bernardes, Gonçalo J. L.
Abstract: Photoactivated drugs provide an opportunity to improve efficacy alongside reducing side‐effects in the treatment of severe diseases such as cancer. Described herein is a photoactivation decaging method of isobutylene‐caged thiols through a UV‐initiated thiol‐ene reaction. The method was demonstrated with an isobutylene‐caged cysteine, cyclic disulfide‐peptide, and thiol‐containing drug, all of which were rapidly and efficiently released under mild UV irradiation in the presence of thiol sources and a photoinitiator. Importantly, it is shown that the activity of histone deacetylase inhibitor largazole can be switched off when stapled, but selectively switched on within cancer cells when irradiated with non‐phototoxic light.